Knockout of Sirtuin 3 in endothelial cells impairs endothelial‐dependent relaxation and myogenic response in mice - Jian‐Xiong Chen; Jin Zhang; Yingjie Chen; Heng Zeng (Physiological Reports)
Abstract Sirtuin 3 has been shown to regulate endothelial function and coronary flow reserve in mice. Knockout of SIRT3 reduced endothelial nitric oxide synthase expression in the mouse hearts. In this study, we investigate whether endothelial SIRT3 regulates vascular function and myogenic responses in distal intramural branches of the left anterior descending coronary artery (CA) and middle cerebral artery (MCA) of mice. Both male and female endothelial SIRT3 knockout (SIRT3ECKO) mice and control SIRT3LoxP mice were used and CA and MCA were dissected and mounted in a myograph system. The myogenic response was evaluated by measuring changes in inner diameter in response to 20 mmHg stepwise increases in intraluminal pressure in PSS (active diameter) and Ca2+‐free PSS (passive diameter). Acetylcholine (Ach)‐induced endothelial‐dependent relaxation (EDR) and sodium nitroprusside (SNP)‐induced endothelial‐independent relaxation (EIR) were examined. Our results showed that the myogenic responses were significantly impaired in both the CA and MCA of SIRT3ECKO mice. Furthermore, female mice had worsened myogenic response in MCA. In CA, EDR was abolished in both male and female SIRT3ECKO mice. Intriguingly, EIR was only reduced in the female mice. In MCA, EDR was reduced in male SIRT3ECKO mice, whereas EIR was decreased in both male and female mice. Female SIRT3ECKO mice had profound dysfunction in CA, whereas male mice exhibited more dysfunction in MCA. These data revealed a sex and organ‐specific role of endothelial SIRT3 in vascular function and myogenic responses. Our study suggests that endothelial SIRT3 is necessary for maintaining vascular function and blood flow autoregulation.